Full-Cycle Rehabilitation Management of Coronary Atherosclerotic Heart Disease in the Elderly - DONG Anqin (康复学报, 2025)
Coronary atherosclerotic heart disease (CAD) is one of the main causes affecting the health of elderly people (≥65 years old). CAD is a threat to the life and health of the elderly, and also brings a huge economic burden to families and society. Elderly individuals frequently present with comorbidities such as hypertension, diabetes, and hyperlipidemia, which seriously exacerbate the occurrence and progression of CAD, thereby imposing heightened demands and challenges for the precise formulation of prevention and treatment strategies in this population. Reducing the recurrence of cardiovascular events, prolonging lifespan, and enhancing quality of life through the full-cycle rehabilitation management have emerged as pivotal research priorities. This article systematically explores the application pathways of the full-cycle rehabilitation management model in the mangement of CAD in the elderly, with a focus on multidimensional intervention strategies, including comprehensive geriatric assessment, pre-disease risk factor management, and post-disease cardiac rehabilitation across the entire disease continuum, aiming to provide scientific guidance for the safety and effectiveness of CAD rehabilitation in the elderly, and promote the development of full-cycle rehabilitation for the elderly with CAD in China.